2020
DOI: 10.2196/19882
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Feasibility, Acceptability, and Efficacy of a Clinical Pharmacist-led Mobile Approach (BPTrack) to Hypertension Management: Mixed Methods Pilot Study

Abstract: Background Hypertension is a prevalent and costly burden in the United States. Clinical pharmacists within care teams provide effective management of hypertension, as does home blood pressure monitoring; however, concerns about data quality and latency are widespread. One approach to close the gap between clinical pharmacist intervention and home blood pressure monitoring is the use of mobile health (mHealth) technology. Objective We sought to investiga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(61 citation statements)
references
References 34 publications
(31 reference statements)
0
59
0
Order By: Relevance
“…Telehealth facilitates more engaging and efficient management of chronic conditions and allows members of the patient care team, such as pharmacists to connect with patients and thereby improve patient outcomes 5,7‐9 . Telehealth interventions by pharmacists can improve the control of blood pressure and reduce serum levels of hemoglobin A1c when compared with the usual standard of care afforded by primary care providers alone 8,10,11 …”
Section: Introductionmentioning
confidence: 99%
“…Telehealth facilitates more engaging and efficient management of chronic conditions and allows members of the patient care team, such as pharmacists to connect with patients and thereby improve patient outcomes 5,7‐9 . Telehealth interventions by pharmacists can improve the control of blood pressure and reduce serum levels of hemoglobin A1c when compared with the usual standard of care afforded by primary care providers alone 8,10,11 …”
Section: Introductionmentioning
confidence: 99%
“…(2020) [35], continuous blood pressure monitoring at home with data entry into a mobile machine and the provision of personalized interventions were effective in controlling blood pressure levels. Thus, a national health care approach that provides home blood pressure monitors can be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Other meta-analyses confirmed reductions in SBP for text messaging interventions (mean difference = −6.1, 95% CI −8.5, −3.8, P < 0.01) [13 ▪ ], and smartphone applications (weighted mean difference = −2.28, 95% CI −3.90, −0.66, P = 0.006) [17]. Individual studies demonstrated a 6.7 mmHg greater reduction in SBP in a tailored mobile-application intervention versus control ( P = 0.10) [16 ▪ ], declines in both SBP (baseline mean 137.3 mm Hg, standard deviation (SD) 11.1, follow-up mean 131.0 mm Hg, SD 9.9, P = 0.02) and DBP (baseline mean 89.4 mm Hg, SD 7.7, follow-up mean 82.5 mm Hg, SD 8.2, P < 0.001) after a 12-week pharmacist-led telehealth intervention [9], and increased odds of BP control associated with tailored monthly phone counseling matched to a patient's stage of change (OR = 1.84, 95% CI 1.28, 2.67, P = 0.001) versus usual care AND monthly phone counseling using nontailored information (OR = 1.48, 95% CI 1.02, 2.14, P = 0.04) versus usual care [19].…”
Section: Evidence For Clinical Outcomesmentioning
confidence: 98%
“…Some studies report provider perspectives on eHealth strategies, documenting concerns about the quality of self-monitored data [9,27 ▪ ] and who holds responsibility for self-monitored clinical data [10]. Implementing eHealth interventions to improve adherence requires training, monitoring, and action on the part of healthcare providers and staff to encourage patient participation and resolve technical issues; the future of insurance reimbursement to support this effort is unclear [27 ▪ ].…”
Section: Provider Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation